Blogging Within Formal and Informal Learning Contexts: Where are the Opportunities and constraints? - Hammond, Michael (Proceedings of the International Conference on Networked Learning, 2006)
This paper presents a small scale exploratory study of blogging within a collaborative project involving the author and a group of seven research student colleagues. Blogs were used for journaling and a joint blog was set up for group discussion. It was found that rates of participation were uneven and in the majority of cases very few entries were posted, however all except one had participated in some way to the joint blog and two students in particular had posted very long entries to their personal journals. Participants valued blogging as it encouraged reflection on ideas; provided feedback from others; and enabled communication to a wider and removed audience. The strongest constraint on blogging was seen as a lack of purpose and audience for personal journaling. It was easier for participants to contribute to the joint blog as there seemed a much more clearly defined audience and purpose. Implications for the study are discussed.